Is LESS/NOTES really more? - Rassweiler, Jens (European urology, 2011)
Apart from the ergonomic inconveniences, LESS surgery presents some specific technical difficulties such as the loss of instruments triangulation, and closer proximity of instruments, leading to clashing and crossing of the instruments both inside and outside the patient. In this case, the surgeons need to adopt a posture particularly appropriate for this task. However, it is not clear whether the movements of the upper-limb joints are able to destabilize other body segments, like it is the head segment. The UCM framework allowed the quantiﬁcation of the overall upper-limb joint variability into a task-relevant and task-irrelevant component. It was supposed that LESS surgery needs more flexibility by the surgeon than conventional laparoscopy, and that could compromise joint coordination. The results of the UCM analysis showed a positive degrees of freedom synergy index indicating that the co-variation of the upper-limb joint angles stabilizes the head posture of the surgeons in the anterior-posterior direction. There was not a statistically significant difference in the synergy index between the LAP and LESS approach for the UCMs of both the left (t(7)=1.76,p = 0.12) and right side joint spaces (t(7)=1.127,p = 0.902). However, important differences can be appreciated individually. The results showed that the underlying framework was able to quantify surgeons’ motor variability, providing inspiration for new human-machine interaction designs, as well as more targeted ergonomics assessments.